Breakfast Consumption Amongst School Children in Northern Iran - Veghari, Gholamreza; Mansourian, Azad Reza (Journal of Nepal Paediatric Society, 2013)
Background: Eating breakfast has an important role for growing and educational promotion in students. This study set out to evaluate skipping breakfast and some related demographic factors among primary school children in the north of Iran in 2008. Material and methods: This is a descriptive and cross-sectional study that performed on 7426 students (3786=male and 3640=female) from 112 schools in urban and rural area. The schools and students were chosen by cluster and stratify sampling. Data collected by questioner for all samples through interview. Spss.win16 software was used for analysis. Findings: Skipping breakfast were shown among 9.3% of students (female= 9.9% and male=6.7%) and in Turkman ethnic groups (6.0%) is significantly less than other ethnic groups such as Fars (9.6%) and Sistani (9.4%) (P=0.001). There is a statistical significant differences between gender and type of school, separately (P=0.001). The most reasons for lack of breakfast eating are low appetite (70.1%), non-flavorful foods (11.8%), inattention of mothers (5.2%) and others factors (13%). Conclusion: Skipping breakfast is one to eleven of students and social-demographic factors such as ethnicity and social level based on type of school effects on it. With regard to roll of breakfast eating in educational promotion, recognition and solving the obstacle factors for eating breakfast in students were recommended. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6095 J. Nepal Paediatr. SocVol.32(3) 2012 193-200